Changes in hardness and resilience of i-gelTM cuffs with temperature: a benchtop study - John Dingley (Anaesthesia, 2018)
The i-gelTM is a supraglottic airway with a gel-like thermoplastic cuff. It has been suggested that the seal against the larynx improves over time. Perhaps the most intuitive explanation proposed for this is cuff softening on warming from ambient to body temperature. We investigated this using a food industry texture analyser machine over a wide temperature range.Size #2 and #3 i-gelsTM were secured to a platform within a temperature-controlled water bath, mounted on a texture analyser test stand. Both water and i-gelTM cuff temperatures were recorded. A spherical probe advanced 4mm into the surface of each i-gelTM at 1mm/s then retracted at the same rate while the upward pressure on the probe was recorded at 200Hz. Three runs made at each of 11 temperatures (10°C to 60°C, 5°C increments) gave 105,864 data points from which values for hardness (the peak force on the probe at maximum indentation), and resilience (the rate at which the material recovers its original shape), were calculated.Over 10°C-60°C the smallest hardness value expressed as a percentage of the largest was 88.2% and 89.8% for #2 and #3 i-gelsTM respectively. For resilience these were 92.8% and 86.2% respectively. Over a room temperature (21°C) to body temperature (37.4°C) range, hardness decreased by 3.15%, and increased by 0.47% for sizes #2 and #3 respectively, with resilience values decreasing by 1.85% and 2.68% respectively.Although cuff hardness and resilience do generally reduce with warming, the effect is minimal, especially over the temperature ranges encountered in clinical use.